SWOT Matrix Based Business Strategy Analysis: Case Study of PT Berkah Utama Transsindo East Lampung - Hanif Hardiansah; RR Erlina; Zainnur M. Rusdi (International Journal of Management Research and Economics, 2025)
PT Berkah Utama Transsindo (Butrans) has experienced a decrease in market share, declining from 74% in 2022 to 62% in 2023, while its competitor, PT Adhitama Surya Abadi Express (ASAE), expanded its share from 26% to 38%. This study examines Butrans’s internal strengths and weaknesses as well as its external opportunities and threats by utilizing the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, alongside SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM) Total Attractiveness Score. The aim is to identify key areas for improvement and prioritize strategic initiatives. The results position Butrans in quadrant IV of the Internal-External (IE) Matrix, indicating a relatively strong strategic stance where internal strengths moderately outweigh external challenges. The analysis highlights major strengths such as an extensive fleet and an integrated vehicle monitoring system, while identifying key weaknesses including high operating costs and limited cargo diversification, which reduce adaptability. Opportunities driven by economic growth and infrastructure expansion are counterbalanced by threats from natural disasters and intensifying competition. To strengthen its market position, the study recommends cost reduction, diversification of services, technological enhancements for greater efficiency, stronger client engagement, and the development of contingency strategies to mitigate external risks. By implementing these recommended strategies, based on insights from the IFE and EFE analyses, Butrans is expected to recover market share and maintain its leadership in the logistics industry of East Lampung.